If it's not what You are looking for type in the equation solver your own equation and let us solve it.
18x+6+36=26x+2
We move all terms to the left:
18x+6+36-(26x+2)=0
We add all the numbers together, and all the variables
18x-(26x+2)+42=0
We get rid of parentheses
18x-26x-2+42=0
We add all the numbers together, and all the variables
-8x+40=0
We move all terms containing x to the left, all other terms to the right
-8x=-40
x=-40/-8
x=+5
| -7(1-6n)=-91 | | 7x+10+2x+7=116 | | -3x+11=-11 | | 15^y+5=7 | | -3-5(x+2)=7x-8+2x | | (5-a)6=36 | | 7t-4=t-10 | | -107=-4x-3(1+3x) | | 18+9x-12x-7=-11 | | x=40+(0,3x) | | 3.x+3=18 | | X=85n | | 112=4(5x+4)-4 | | 2(x+4)+4x-6=6(8+2x)-6 | | 4=3x7 | | x-0,3x=40 | | 9x-80=4x-10 | | 9b+9=126 | | c+9=-2c-9 | | 2x=8=5x+2 | | 6+4u=5u | | 6v-8=6+4v | | 13x=7=215 | | -4q-9=-7q+9 | | v−7=9+12. | | 10=4x=3x+56 | | 2x+10=-26+7x | | 9n-2n-2n=15 | | x^2-2x-70=50 | | 6v-6v+4v=4 | | -g+10=g-10+2g | | .7-4x=1.3 |